897. SYMPHYOTRICHUM VAHLII: Compositae. (4th January 2019) - Hind, Nicholas; Strange, Kit
Summary: Symphyotrichum vahlii (Gaudich.) G. L. Nesom (Compositae: Astereae: Symphyotrichinae) is described and illustrated, and the species is provided with an expanded synonymy that includes type citations, known types, and supplementary comments. Notes are provided on cultivation and propagation. Comments are also made on the historical collections representing this species, both as types and early collections, and relating these to early circumnavigations. The likelihood that Thinobia araucana Phil., of the monotypic Thinobia Phil., is this species is also discussed.